Quantificação de flavonoides totais da eruca sativa (rúcula) cultivada de forma hidropônica na região oeste do Paraná - Malikosky, Monique (2020)
The vegetable Eruca sativa, popularly known as arugula, has several health benefits, such as anti-inflammatory and antioxidant activities in living organisms, as it contains proteins, vitamins A and C, mineral salts such as iron and calcium, and flavonoids. Flavonoids have received a lot of attention in recent years due to the various beneficial effects, which can mention the most important, it helps in the antiinflammatory process, in the symptoms of menopause, it prevents some types of cancer and it helps to maintain heart health. The work aimed to quantify the total flavonoids of the arugula produced in a hydroponic way in the western region of Paraná, using different extraction methods, temperatures and forms of agitation, in addition to also considering the plant cultivation time. Its activities were also evaluated: antimicrobial, antifungal and antioxidant. First, probative tests were carried out, varying the concentration of methanol as the extraction solvent for flavonoids, in order to identify an efficient method for performing all other steps. The fresh vegetable material was cut manually, using 5 g of the chopped vegetable leaves in 100 mL of solvent mixture with the humidity determined in 92%. The tests were continued with the shaker stirring process at 170 rpm, in triplicates at an ambient temperature of 25 ° C and 55 ° C, the extraction time varying by 12, 24, 36 and 48 h and the plant cultivation time , in 7.14 and 21 days. After obtaining the extracts, the total flavonoids were read on the UV-Vis spectrophotometer at 440 nm wavelength, compared to the standard quercetin curve. For the tests carried out, the most satisfactory result was with the solvent concentration of 80% MeOH, in the extraction times of 12 and 24h. At the end, it used the ANOVA and Tukey test (p <-0.05) where it was observed that for the extraction procedure with the Shaker, the best results were obtained when the temperature of 55 ° C was used in 12 h of extraction with the plant grown for 7 days. For the antimicrobial tests, the results were interpreted based on the fact that the more flavonoids present in the extract, the greater the halo of inhibition. In the antioxidant activity using the methods of DPPH and hydrogen peroxide, the conclusion was reached that the activity is directly proportional to the concentration of flavonoids in the plant.